Penderitaan Tanpa Ukuran: Mengapa KUHAP Harus Segera Mengatur Kerugian Imateriil? - Utami, Setiani Budi; Frans, Mardian Putra (Jurnal Hukum & Pembangunan, 2025)
Law enforcement must ensure that the justice process operates in accordance with the principles of true justice. The criminal justice system in Indonesia emerged as a response to public dissatisfaction with the performance of law enforcement agencies that overly emphasized formal law and order alone, without regard for human dignity. The preamble of the Criminal Procedure Code (KUHAP) affirms that this system aims to protect human dignity, thus substantive justice must be prioritized. In this context, human rights, particularly the protection of crime victims, become crucial. However, in practice, victims are often marginalized, especially regarding compensation for immaterial damages that lack clear regulation in the current Criminal Procedure Code. Survey results and statistical data show a significant increase in cases of bullying, cyberbullying, and crimes against morality, which cause psychological suffering to victims. The legal vacuum in calculating immaterial damages risks creating injustice and abuse of authority in judicial processes. This research employs a normative juridical approach, using library research methods on legislation, legal doctrines, and relevant jurisprudence. This study aims to analyze the urgency of regulating immaterial damages in Indonesia's criminal justice system and to formulate normative ideas regarding fair compensation assessment mechanisms for crime victims. The expected outcome is that this article will make an important contribution to filling the literature gap while supporting national legal reform through a restorative justice approach.